Real‐world application of plasmapheresis for neurological disease: Results from the Japan‐Plasmapheresis Outcome and Practice Patterns Study. Issue 1 (17th July 2022) - Lin, Youwei; Oji, Satoru; Miyamoto, Katsuichi; Narita, Tomoko; Kameyama, Mana; Matsuo, Hidenori
Abstract: Introduction: Plasmapheresis is a well‐recognized treatment for autoimmune neurological diseases in Japan. However, the practice varies depending on the facility, and the actual treatment conditions are unclear. Methods: To clarify real‐world conditions, a prospective observational study was conducted on patients with neurological diseases who were scheduled to receive plasmapheresis. A dataset was analyzed that included 887 treatments from 210 patients with myasthenia gravis (MG), multiple sclerosis (MS), neuromyelitis optica spectrum disorders (NMOSD), and other diseases for 82, 30, 24, and 74 patients, respectively. Results: The types of plasmapheresis performed included immunoadsorption plasmapheresis, plasma exchange, and double filtration plasmapheresis with 620, 213, and 54 treatments, respectively. Approximately, 60% of the treatments were performed using peripheral blood access alone. Non‐serious adverse events were observed in 10 patients. Conclusions: A statistically significant improvement was observed after plasmapheresis in patients with MG, MS, and NMOSD. These were evaluated using the modified Rankin Scale.